Steels tribological parameters in treated by the magnetic field lubricating environments / M.N. Svirid, A.P. Kudrin, L.B. Pryimak // Problems of Tribology. – 2012. – № 1. – Р. 52-54. - Свирид, М.Н.; Кудрин, А.П.; Приймак, Л.Б. (Problems of Tribology, 2014)
In the article the influence of the magnetic field on the lubricating materials modifying additions and steels tribological parameters in treated by the magnetic field working environments is determined.